Lichen sclerosus and lichen planus overlap syndrome in a menopausal woman - Rotsztejn, Helena; Krawczyk, Tomasz (Menopause Review/Przegląd Menopauzalny, 2003)
A case of lichen planus and lichen sclerosus in one patient is reported. It is a rare coexistence of clinically similar diseases or an overlap syndrome often met in autoimmune diseases.